2020
DOI: 10.1002/ange.202000247
|View full text |Cite
|
Sign up to set email alerts
|

Redox Stability Controls the Cellular Uptake and Activity of Ruthenium‐Based Inhibitors of the Mitochondrial Calcium Uniporter (MCU)

Abstract: The mitochondrial calcium uniporter (MCU) is the ion channel that mediates Ca2+ uptake in mitochondria. Inhibitors of the MCU are valuable as potential therapeutic agents and tools to study mitochondrial Ca2+. The best‐known inhibitor of the MCU is the ruthenium compound Ru360. Although this compound is effective in permeabilized cells, it does not work in intact biological systems. We have recently reported the synthesis and characterization of Ru265, a complex that selectively inhibits the MCU in intact cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…In contrast, our present study shows that MCU inhibition (genetic ablation of mcu-1 and Ru360 treatment) ameliorated muscular function decline with age and DMD in C. elegans . Recently, MCU-1 inhibitors, which are also ruthenium compounds with improved in vivo permeability such as Ruthenium Red and Ru265, have been developed and are being investigated as potential therapeutic agents for cardiac dysfunctions 30,31 . These findings suggest MCU has an evolutionarily conserved role in muscle health.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, our present study shows that MCU inhibition (genetic ablation of mcu-1 and Ru360 treatment) ameliorated muscular function decline with age and DMD in C. elegans . Recently, MCU-1 inhibitors, which are also ruthenium compounds with improved in vivo permeability such as Ruthenium Red and Ru265, have been developed and are being investigated as potential therapeutic agents for cardiac dysfunctions 30,31 . These findings suggest MCU has an evolutionarily conserved role in muscle health.…”
Section: Resultsmentioning
confidence: 99%
“…In previous electrochemical studies of Ru265 in aqueous solutions, this feature was not observed, presumably due to the smaller accessible potential window within water. 26,59 Both RuOBz and RuOFc have more negative reduction potentials of −1.27 V and −1.35 V, respectively, than Ru265′ (−1.07 V). The more negative redox potentials of these compounds are consistent with the electrochemical Lever parameters of carboxylates compared to water, 62,63 which reflect the greater donor strength of these carboxylate ligands.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…As such, the pseudo-first-order rate constants obtained via UV-vis spectroscopy represent the rate-determining loss of the first carboxylate ligand. 26,27,29 The aquation half-lives in pH 7.4 buffer at 37 °C for RuOBz and RuOFc are 6.5 and 2.9 h, respectively, within the range of other carboxylate-capped Ru265 complexes whose half-lives span 3.3-9.9 h. 29 Notably, the aquation rate constant of RuOFc is approximately two times greater than that of RuOBz, despite the fact that the axial Ru-O distances within these complexes are indistinguishable and the donors strengths of ferrocenecarboxylate and benzoate are similar, as reflected by the pK a values of their conjugate acids (Table 1). The faster aquation kinetics of RuOFc may therefore be a con- sequence of a lower energy transition state, rather than a difference in the thermodynamic ground states of the complexes.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…RuRed was purchased from Sigma-Aldrich (Cat. # R2751), and Ru265, Ru270 and Ru360', and other ruthenium complexes were synthesized as previously described (33,34,(59)(60)(61)(62)(63)(64)(65)(66). All compounds were dissolved in water.…”
Section: Bacterial Strains Media and Compoundsmentioning
confidence: 99%